TRENDS IN THE INCIDENCE OF RHEUMATIC DISEASES IN THE ADULT POPULATION OF RUSSIA OVER 2010–2014 - R. M. Balabanova; T. V. Dubinina; Sh. F. Erdes (Научно-практическая ревматология, 2016)
The analysis covering the five-year period (2010–2014) showed that the adult population of the Russian Federation showed increases in the incidence of rheumatoid arthritis (RA), estimated per 100,000 population, by 5%, in that of spondylopathies (SP), osteoarthritis (OA), and osteoporosis (OP) by 32.2, 12.1, 7.3%, respectively, and an 8.6% decrease in that of only reactive arthropathies (ReA); the incidence of psoriatic arthritis (PsA) and systemic connective tissue diseases was virtually unchanged with increment of 1.3 and 0.3%, respectively. Our attention is engaged by the high incidence of RA (300.7) in the North Caucasian (NC) Federal District (FD) with a considerable increment (+30%) over the 5 years and by that in the Volga (V) FD throughout the analyzed period (342.4 in 2014). The incidence of SP higher than Russia's average was noted in the NCFD (124.5) with a 48.4% increment by 2014 and in the Far Eastern FD (136.1 with a 47.5% increment); and that was especially high in the Crimean (C) FD (380.0). The incidence of ReA remained constantly high in the NCFD (as high as 129.0 in 2014); on the contrary, it turned out to be very low in the CFD (7.8%). Only the NCFD showed a higher than average incidence of PsA (59.0) throughout the analyzed period in Russia. In 2014 the incidence of OA below Russia's average was seen in the NCFD (1893.3) and CFD (1875.8). The high incidence of OP was observed in the Ural (148.9) and Siberian (228.2) FDs. At the same time it was low in a number of FDs: the Southern FD (54.1), NCFD (68.7), and VFD (89.9) and very low in CFD (36.7).